2013
DOI: 10.1155/2013/895045
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adipokines and Bone Metabolism

Abstract: Osteoporosis is a serious social issue nowadays. Both the high morbidity and its common complication osteoporotic fracture load a heavy burden on the whole society. The adipose tissue is the biggest endocrinology organ that has a different function on the bone. The adipocytes are differentiated from the same cell lineage with osteoblast, and they can secrete multiple adipokines with various functions on bone remolding. Recently, several novel adipokines have been identified and investigated thoroughly. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 90 publications
1
49
0
2
Order By: Relevance
“…Adipokines control insulin sensitivity, neuroendocrine activity, food and water intake, breeding, inflammatory response, cardiovascular function, and bone metabolism [16][17][18]. Recently, lots of new adipokines have been discovered such as adiponectin, leptin, resistin, chemerin, omentin, vaspin, and visfatin [18]. These adipokines might participate in the bone metabolism through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipokines control insulin sensitivity, neuroendocrine activity, food and water intake, breeding, inflammatory response, cardiovascular function, and bone metabolism [16][17][18]. Recently, lots of new adipokines have been discovered such as adiponectin, leptin, resistin, chemerin, omentin, vaspin, and visfatin [18]. These adipokines might participate in the bone metabolism through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, adipokines and bone metabolism have a close relationship, which received a lot of attention in both clinical and biological research [17,18]. Previous studies suggested that adipokines such as adiponectin, leptin, resistin, visfatin, vaspin, chemerin, and omentin-1 could modulate bone metabolism both in vitro and/or in vivo [18].…”
Section: Introductionmentioning
confidence: 99%
“…Testosteron sadece prostat kanser gelişiminde değil aynı zamanda Benign prostat hiperplazisinin (BPH) patogenezinde aktif rol oynamaktadır [39,40]. Prostatın büyümesi ve gelişiminin testesteron ve onun aktif metaboliti olan dihidrotestesteronun (DHT) etkisi altında gerçekleştiği ve BPH'nin oluşması için androjen reseptörlerinin DHT ile stimülasyonun gerekli olduğu Yağ dokunun, aktif endokrin organ gibi birçok hormon ve sitokin salgıladığı bilinmektedir [44][45][46]. Yağ doku kitlesindeki artışın, kanser gelişiminde bir risk faktörü olduğu [47] ve yüksek kalorili diyetlerin kanser etiyolojisinde rol oynadığı bilinmektedir [48].…”
Section: Discussionunclassified
“…Apelin is an adipokine released from the adipose tissue that is accepted to be an endocrine tissue (2,3). Apelin has been detected in the endothelium of the vessel wall as well as the heart and peripheral organs in the humans (4).…”
Section: Introductionmentioning
confidence: 99%